2015
DOI: 10.1007/s10517-015-2883-z
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Correction of Regulatory Volume Decrease Evoked by Hypotonic Stress in Mouse Oocytes In Vitro

Abstract: Regulatory volume decrease in response to hypotonic stress is typical of the oocytes and early mouse embryos. Changes in the kinetics of osmotic reaction can be used as a marker of the modulating effect of the incubation medium on transmembrane transport in embryonic cells. Quantitative laser scanning microtomography (QLSM) was used to measure oocyte volume. In this paper, it is shown that addition of 5 μM glycine, taurine, or GABA, as well as ATP to Dulbecco's medium abolished the regulatory volume decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Definite evidence determines that activation of VSOR Cl − channel is concerned with cardiac contractile dysfunction [22, 24, 25], however DCPIB may attenuate cardiomyocyte apoptosis and rescue cardiac function by inhibition of VSOR Cl − channel-activated [2629]. The present study proposes a novel evidence that VSOR Cl − channel-activated by ROS may cause autophagic cell shrinkage, leading to intracellular acidification and autophagy-related cell death.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Definite evidence determines that activation of VSOR Cl − channel is concerned with cardiac contractile dysfunction [22, 24, 25], however DCPIB may attenuate cardiomyocyte apoptosis and rescue cardiac function by inhibition of VSOR Cl − channel-activated [2629]. The present study proposes a novel evidence that VSOR Cl − channel-activated by ROS may cause autophagic cell shrinkage, leading to intracellular acidification and autophagy-related cell death.…”
Section: Discussionmentioning
confidence: 64%
“…Cell death such as apoptotic and necrotic cell death are associated with alterations of cell volume regulation, the control of cell volume is essential not only for maintaining physiological cell activities but also for cell survival. The RVD may be caused by activation of VSOR Cl − channel in many mammalian cell [22, 24, 30]. Moreover, the RVD is abolished when a blocker of VSOR Cl − channel DCPIB is added [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells are exposed to various osmotic changes in vivo. A previous report has shown that cell volume increases because of water flow into the cell in a hypotonic environment (Pogorelova et al, 2015). Although cells are forced to change their volume according to extracellular environments with varying osmolalities, cells have a system to resist volume variations and maintain a stable volume.…”
Section: Discussionmentioning
confidence: 99%
“…The VSOR Cl -channel is the key to the occurrence of apoptosis by inducing apoptotic volume decrease (AVD), a major hallmark of cell apoptosis and an early prerequisite to apoptotic events. Observed soon after cell swelling, the regulatory volume decrease (RVD) is completed by parallel activation of the VSOR Cl -channels in numerous cell types [13,14]. In addition, non-swelling-coupled activation of the VSOR Cl -channels is believed to cause AVD in many cells [15,16].…”
Section: Introductionmentioning
confidence: 99%